A Review of the Philippine Qualifications Framework : Towards Improved Skills Recognition and Mobility - World Bank (World Bank, Washington, DC, 2021)
The Philippines increasingly emphasizes lifelong learning and skills mobility for labor productivity as an integral part of the country’s growth strategy. The Philippine Development Plan 2017-2022 presents a series of activities to improve labor productivity through human capital investment. Investment in this area is critical given that the country’s growth has benefited from a steady structural transformation shifting resources from low- to high-productivity of remittances from Overseas Filipino Workers (OFWs). Aside from improvements in basic education requirements, an important milestone in the country’s skills development came with the introduction of the national qualifications system known as the Philippine Qualifications Framework (PQF). To ensure that the PQF remains responsive to the skills demand and needs of the international and domestic labor markets and fully achieves its mandate, the PQF Act requires regular reviews and updates of the framework. This PQF review, the first of its kind, aims to assess various aspects of the framework. The remainder of this report consists of four sections. Section 2 provides a brief country background of the Philippines to put the discussions into context. Section 3 presents findings from the PQF review concerning the PQF’s design, implementation, and utilization. Section 4 presents policy recommendations and discussions, and Section 5 concludes.